1976
DOI: 10.1001/archderm.112.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Scleromyxedema

Abstract: An unusual, nodulocystic form of scleromyxedema (lichen myxedematosus) developed in a 48-year-old man with a six-year history of psoriasis. The scleromyxedema responded to intermittent therapy with melphalan and prednisone. Dermabrasion smoothed and softened the skin and increased the mobility of the perioral skin. Two months after remission of the skin lesions, psoriasis recurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…An unusual nodulocystic form on the face was successfully treated with melphalan [27]. An extensive nodular variant on the face regressed after radiation therapy [16].…”
Section: Discussionmentioning
confidence: 99%
“…An unusual nodulocystic form on the face was successfully treated with melphalan [27]. An extensive nodular variant on the face regressed after radiation therapy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Review bone marrow examination is more often normal. Myeloma was recorded by Perry, Montgomery & Stickney (i960) but this was not confirmed on follow-up (Wright et al, 1976). Jablonska & Stachow (1972) reported a patient with IgG kappa myeloma and diffuse 'sclerodermatous' skin involvement who presumably had scleromyxoedema, although this possibility was not considered by the authors.…”
Section: Lichen Myxoedematosusmentioning
confidence: 95%
“…Certain authors have suggested that the paraprotein should be considered as essential for the diagnosis (Hill, Crawford & Rogers, 1976) but there are several reports of clinically typical cases were no paraprotein has been detected (Rudner, Mehregan & Pinkus, 1966;Rowell, Waite & Scott, 1969;Tay & Khoo, 1970;Howsden, Herndon & Freeman, 1975;Jessen, Straight & Becker, 1978). Some cases have responded favourably to cytotoxic therapy (Feldman et al, 1969, Wright et al, 1976, which suggests that the paraprotein is of some aetiological importance, but the cases that responded were not always the ones with associated gammopathies (Howsden et al, 1975;Jessen et al, 1978). One case of lichen myxoedematosus showed spontaneous resolution despite the persistence of the paraprotein (Hardie et al, 1979).…”
Section: Lichen Myxoedematosusmentioning
confidence: 99%